Studi Deskriptif Penyebab Kejadian Ketuban Pecah Dini (KPD) pada Ibu Bersalin - Budi Rahayu; Ayu Novita Sari (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
Premature Rupture Membranes is a rupture of the membranes prematurely. KPD Cause not known with certainty, but nothing to do with uterine hypermotility, thin membranes, infections, multiparous, maternal age, location of the fetus, and previous history of premature rupture of membranes. Impact of the KPD can cause maternal or neonatal infection, hypoxia or compression of the umbilical cord, fetal deformity syndrome, increased Caesarean labour or normal delivery failure, and increased morbidity and maternal perinatal mortality. This study was to identify the cause of the incident picture premature rupture in women giving birth in hospitals in Yogyakarta. This study uses descriptive design quantitative used retrospective time approach. The population in this study are all mothers who have premature rupture of membranes in hospitals in Yogyakarta in obtained from medical records. Premature rupture of membrane in Yogyakarta Hospital there are 427 cases. A sampling technique that with a total sampling with 427 respondents. Analysis of the data used univariate analysis. The results that most respondents are multipara many as 245 people (57.4%), aged 20-35 years as many as 265 people (62.1%), gestational age ≥37 weeks as many as 343 people (80.3%), over distensi uteri as many as 410 people (96.1%), where the fetus head presentation many as 396 people (92.7). In conclusion, an overview of the causes of premature rupture events on maternal includes multipara, 20-35 years of age, gestational age ≥37 weeks, normal uterine enlargement, and the location of the fetus normal presentation.